Akurasi Diagnostik dan Analisis Gambaran Sitomorfologi Sikatan Bilier dan Endoscopic Ultrasound Guided Fine Needle Aspiration (EUS-FNA) Pankreas Berdasarkan The Papanicolaou Society of Cytopathology System - Sarwanti; Marini Stephanie (Majalah Patologi Indonesia, 2022)
BackgroundEndoscopic ultrasound guided fine needle aspiration (EUS-FNA) of the pancreas and biliary brushes is a minimally invasive method ofcytology sampling. The purpose of this study was to determine the sensitivity, specificity, and accuracy of examination of biliary brushcytology and EUS-FNA pancreas based on the System of standardized terminology and nomenclature for pancreatobilliary cytology(STNPC) as well as cytology characteristics of pancreatic malignancy.MethodsA search of the biliary brush preparation and EUS-FNA pancreatic in 2017-2020 was carried out in the Archives section of the Department ofAnatomical Pathology FKUI / RSCM. 506 cases of biliary brush cytology and EUS-FNA pancreatic, conducted a search of histopathologicalpreparations and re-categorized based on STNPC.ResultsCytological cases of biliary brushing and pancreatic EUS-FNA paired with histopathology in 2017-2020 151 cases, 85 cases of biliarybrushing and 66 cases of pancreatic EUS-FNA, were re-categorized based on STNPC with results of biliary brushing 27 non-diagnosticcases, 24 atypical cases, 7 suspicious for malignancy (SFM) cases and 17 malignant cases. Meanwhile, for pancreatic EUS-FNA cytology16 non-diagnostic cases, 2 negative cases, 16 atypical cases, 3 other neoplasms, 4 SFM cases and 25 malignant cases. Twenty sevencases of false negative biliary brushes on non-diagnostic and atypical preparations and 4 cases of false negative on pancreatic EUS-FNA onnon-diagnostic and atypical preparations. Biliary brushing diagnostic test results: sensitivity 82.35%, specificity 100%, positive predictivevalue (PPV) 100%, negative predictive value (NPV) 84.21% and accuracy 90.9%. In pancreatic EUS-FNA: sensitivity 84.21%, specificity100%, PPV 100%, NPV 986.67% and accuracy 92.86%.ConclusionCytological diagnosis of biliary brushing and pancreatic EUS-FNA has good specificity, sensitivity and accuracy, but definitive diagnosisrequires histopathological examination